2008
DOI: 10.3802/jgo.2008.19.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Value of pelvic examination and imaging modality for the evaluation of tumor size in cervical cancer

Abstract: Objective: The purpose of this study was to compare the accuracy of pelvic examination versus imaging modality such as computed tomography (CT) or magnetic resonance imaging (MRI) in the measurement of the tumor size of invasive cervical carcinoma based on pathologic findings. Methods: Patients with stage Ib-II cervical cancer who underwent primary surgical treatment between January 2003 and December 2005 were evaluated retrospectively. One hundred three consecutive patients aged 24 to 81 years (mean age, 50.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the present study, tumor size was evaluated during pelvic examination with a low accuracy of 70.5% (with a difference of less than 1.0 cm), similar to a previous report [22]. A smaller tumor size (≤2 cm; postoperative gross measurement) was the only independent favorable factor for both PI and VI for women with stage IA2-IB1 cervical cancer.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, tumor size was evaluated during pelvic examination with a low accuracy of 70.5% (with a difference of less than 1.0 cm), similar to a previous report [22]. A smaller tumor size (≤2 cm; postoperative gross measurement) was the only independent favorable factor for both PI and VI for women with stage IA2-IB1 cervical cancer.…”
Section: Discussionmentioning
confidence: 91%
“…It has been demonstrated that the accuracy of pelvic examination in the measurement of primary tumor size of cervical cancer is approximately around 50% with a difference of 0.5 cm 16 and 50% to 72% with a difference of less than 1.0 cm. 16,17 The accuracy of MRI in the measurement of primary tumor size ranged from 39.8% 16 to 70% 18 with a difference of 0.5 cm and 55.3% with a difference of 1.0 cm. 16 In comparison with other studies, we also used the difference of 0.5 or 1.0 cm as an error range to evaluate the measurement accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The accuracy of MRI in the measurement of primary tumor size ranged from 39.8% 16 to 70% 18 with a difference of 0.5 cm and 55.3% with a difference of 1.0 cm. 16 In comparison with other studies, we also used the difference of 0.5 or 1.0 cm as an error range to evaluate the measurement accuracy. The accuracy of MRI in preoperative measurement of the primary tumor size is 39.60% (with error range T0.5 cm) and 61.39% (with error range T1.0 cm), whereas the accuracy of pelvic examination is 24.75% (T0.5 cm) and 43.56% (T1.0 cm), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The reported accuracy of manual examination in determining the cervical tumor diameter is approximately 50%. 12,13 Magnetic resonance imaging (MRI) has been shown to be useful in the assessment of tumor diameter in patients with cervical carcinoma, with an accuracy of 83% to 93%, and recently, its use in preoperative evaluation has become more and more common in the practice of gynecologic oncology. 14Y18 Although several previous studies addressed the correlation between tumor diameter and other pathological prognostic factors, and other studies utilized MRI as an adjunct to the preoperative staging by manual examination, there have been no previous studies directly addressing the association between the tumor diameters measured preoperatively using MRI and other prognostic factors evaluated with postsurgical pathological examination.…”
mentioning
confidence: 99%